ISLAM BERWAJAH INDONESIA - Sopiyan, Muhtar (Islamic University of Indonesia, 2010)
Islamic Thought in Indonesia from time to time growing. This development will certainly bring consequences pro and conts. This affects the progress of Islamic thought thinking itself. In conjunction with the local culture in Indonesia, Islam in Indonesia has so far considered to be more tolerant. Tolerance is indicated by the accommodating attitude towards the local culture. This attitude reflects the ability and willingness of Muslim Indonesia to absorb the local culture become part of Islamic teachings. Culture is seen as an inherent part of community life, making it impossible for a movement that took the breath rahmatan lilalamin suppress something that has become part of the community. It can not be denied that Allah revealed Islam. in the Arab world, but this does not mean that all the smelly arab identical with Islam. This article tries to discuss briefly the growing Islamic thought in Indonesia, which developed at this time and effort to make Islam the Muslims in Indonesia for more faceless face of Indonesia.